Second line of therapy for gastrointestinal stromal tumors: is there a choice? - L. M. Kogonia; A. M. Koroleva (Медицинский совет, 2019)
Gastrointestinal stromal tumors (GISTs) are rare mesenchymal tumors. Currently, it is possible to carry out three consecutive lines of target therapy against metastatic GISTs: imatinib as first-line, sunitinib as second line and regorafenib as third line. The mutation status of the C-Kit gene is a predictor of GIST sensitivity to imatinib and sunitinib. Some patients have to stop the treatment due to sunitinib related toxicity. Regorafenib can be used as the second line therapy of metastatic GISTs in case of sunitinib intolerance.